Accurate costs of blood transfusion: a microcosting of administering blood products in the United Kingdom National Health Service. Issue 4 (30th January 2018) - Stokes, Elizabeth A.; Wordsworth, Sarah; Staves, Julie; Mundy, Nicola; Skelly, Jane; Radford, Kelly; Stanworth, Simon J.
Abstract : BACKGROUND: In an environment of limited health care resources, it is crucial for health care systems which provide blood transfusion to have accurate and comprehensive information on the costs of transfusion, incorporating not only the costs of blood products, but also their administration. Unfortunately, in many countries accurate costs for administering blood are not available. Our study aimed to generate comprehensive estimates of the costs of administering transfusions for the UK National Health Service. STUDY DESIGN AND METHODS: A detailed microcosting study was used to cost two key inputs into transfusion: transfusion laboratory and nursing inputs. For each input, data collection forms were developed to capture staff time, equipment, and consumables associated with each step in the transfusion process. Costing results were combined with costs of blood product wastage to calculate the cost per unit transfused, separately for different blood products. Data were collected in 2014/15 British pounds and converted to US dollars. RESULTS: A total of 438 data collection forms were completed by 74 staff. The cost of administering blood was $71 (£49) per unit for red blood cells, $84 (£58) for platelets, $55 (£38) for fresh‐frozen plasma, and $72 (£49) for cryoprecipitate. CONCLUSIONS: Blood administration costs add substantially to the costs of the blood products themselves. These are frequently incurred costs; applying estimates to the blood components supplied to UK hospitals in 2015, the annual cost of blood administration, excluding blood products, exceeds $175 (£120) million. These results provide more accurate estimates of the total costs of transfusion than those previously available.